WESTERN BALKAN COUNTRIES ON THE ROAD OF EUROPEAN INTEGRATION: RESULTS AND TENDENCIES - Morari, Cristina (Centre for European Studies, 2012)
The article analyses the negotiations between European Union and countries of the Western Balkans and attempts to identify where the major problems are likely to be. The main obstacles in the process of European integration of the countries from Balkan region are analyzed. Also, the paper focuses on the key priorities that Western Balkan countries have to accomplish in order to reach the domestic readiness for their process of European integration. An important goal of the article is to identify some important conclusions for the European roadmap of the Republic of Moldova from experience of the presented states. [ABSTRACT FROM AUTHOR]
Keywords: european integration; negotiations; pre-accession domestic tasks; Western Balkan countries